Individual and Combined Influence of ACE and ACTN3 Genes on Muscle Phenotypes in Polish Athletes. Issue 10 (October 2018) - Orysiak, Joanna; Mazur-Różycka, Joanna; Busko, Krzysztof; Gajewski, Jan; Szczepanska, Beata; Malczewska-Lenczowska, Jadwiga
Abstract : Abstract: Orysiak, J, Mazur-Różycka, J, Busko, K, Gajewski, J, Szczepanska, B, and Malczewska-Lenczowska, J. Individual and combined influence of ACE and ACTN3 genes on muscle phenotypes in polish athletes. J Strength Cond Res 32(10): 2776–2782, 2018—The aim of this study was to examine the association between angiotensin-converting enzyme ( ACE ) and α-actinin-3 ( ACTN3 ) genes, independently or in combination, and muscle strength and power in male and female athletes. The study involved 398 young male ( n = 266) and female ( n = 132) athletes representing various sport disciplines (ice hockey, canoeing, swimming, and volleyball). All were Caucasians. The following measurements were taken: height of jump and mechanical power in countermovement jump (CMJ) and spike jump (SPJ), and muscle strength of 10 muscle groups (flexors and extensors of the elbow, shoulder, hip, knee, and trunk). The insertion-deletion (I/D) polymorphism of ACE and the R577X polymorphism of ACTN3 were typed using polymerase chain reaction (PCR) and polymerase chain reaction—restriction fragment length polymorphism (PCR-RFLP), respectively. The genotype distribution of the ACE and ACTN3 genes did not differ significantly between groups of athletes for either sex. There was no association between ACE and ACTN3 genotypes (alone or in combination) and sum of muscle strength, height of jump or mechanical power in both jump tests (CMJ and SPJ) for male and female athletes. These findings do not support an influential role of the ACE and ACTN3 genes in determining power/strength performance of elite athletes.